ELECTRONICAL DOCUMENTATION IN THE PROCESS OF EDUCATION, ITS ADVANTAGES, DISADVANTAGES AND BASIC CHARACTERISTICS - MONKA, Peter; MONKOVÁ, Katarína (Trends in education, 2008)
The article deals with the advantages and disadvantages of electronical documentation, there are described the basic characteristics and most used formats of electronical documentation in the article. This form of documentation as the part of today's life sinks into educational field, too, where it is possible to fully use its advantages. The paper was written thanks to support provided by the project KEGA 3/5173/07.
Keywords: electronical documentation; 3D model; software; the format